Institutional Factors Influencing CSR among Korean Firms - Jun, Gyung-Ju(전경주) (대한경영학회지, 2013)
Corporate social responsibility (CSR) is increasing in importance in companies today. Using institutional perspective, we will explore why profit-oriented firms would get involved in CSR and expend their profits and resources on nonprofitable activities. Companies can get involved in CSR as part of their reciprocation to society. However, when it has become generally commonplace for many companies to get involved in CSR, it is difficult to say that companies get involved simply out of altruism. Some Korean companies do get involved in CSR with altruistic motives, but they also get involved due to environmental factors. In this paper, I want to discuss what factors influence Korean firms to get involved using institutional perspective. Korean culture's collectivistic and Confucius characteristics, gaining legitimacy to avoid sanctions, and managing image control may be some of reasons why companies have involved themselves in CSR. If we understand the factors that are operating behind companies' participation in work traditionally carried out by the government and nonprofit organizations, we can consider policies and structural regulations to promote broadly and encourage corporations to move in the direction that benefits the society and themselves. Since this paper explores the theoretical aspects, future research can pursue empirical findings to further examine what are proposed here. KCI Citation Count: 2